Respuesta :
The point (x, y) when reflected across the x-axis becomes (x', y') = (x, -y)
The point (x, y) when reflected across the y-axis becomes (x', y') = (-x, y)
The point (x, y) when reflected across the line y = x becomes (x', y') = (y, x)
The point (x, y) when reflected across the line y = -x becomes (x', y') = (-y, x)
The point (x, y) when reflected across the y-axis becomes (x', y') = (-x, y)
The point (x, y) when reflected across the line y = x becomes (x', y') = (y, x)
The point (x, y) when reflected across the line y = -x becomes (x', y') = (-y, x)
Answer:when the shape reflects about the line y=x, the x-coordinate and the y-coordinate of each point are swapped
Step-by-step explanation: